Experimental study of bituminous mastic behaviour using different fillers based on the ucl method - Movilla-Quesada, Diana; Vega-Zamanillo, Angel; Calzada-Pe´rez, Miguel Angel; Castro-Fresno, Daniel (Journal of Civil Engineering and Management, 2013)
This research demonstrates that the use of suitable amounts of calcium hydroxide as an additive in asphalt mixtures can improve the aggregate-bitumen adhesion, forming a bituminous mixture which is more resistant to traffic loads and the action of water. The analysis was performed using the UCL method and the Cantabrian Test, taking as a case study three types of filler with different natures, mixed with 4.5% bitumen. The results are presented as state curves, which show clear differences between the three fillers, demonstrating that the hydroxide suffers small wear losses in concentrations close to 1.3%, indicating a significant reduction in the risk of plastic deformation, and an improvement in the mixture durability and/or adhesiveness.